2022
DOI: 10.3390/fluids7030095
|View full text |Cite
|
Sign up to set email alerts
|

Particle Transport Velocity in Vertical Transmission with an Airlift Pump

Abstract: This paper presents the optimal conditions for fast transfer of solid particle with an airlift pump. The experimental examinations were carried out in an airlift pump with a length of 5.64 m and an inner diameter of 0.102 m in order to determine the impact of submergence ratio, air flow, and physical particle properties, such as shape, size, and density, on the vertical velocity of the particle in detail. The results showed that with the same air flow, the maximum particle velocity was achieved when the churn … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Compared with the traditional mining method, the air-lifting pump has the advantages of simple structure, low cost, high safety and reliability, and less environmental pollution, so it has become the focus of research. Enany (Enany et al, 2021) conducted an experimental study on the air-lifting pump under different air intake and submerged rates, and the results showed that the optimal value of the liquid phase efficiency of the air-lifting pump under the same intake air amount is between 0.6 and 0.75 for the submerged rate. Catrawedarma I.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with the traditional mining method, the air-lifting pump has the advantages of simple structure, low cost, high safety and reliability, and less environmental pollution, so it has become the focus of research. Enany (Enany et al, 2021) conducted an experimental study on the air-lifting pump under different air intake and submerged rates, and the results showed that the optimal value of the liquid phase efficiency of the air-lifting pump under the same intake air amount is between 0.6 and 0.75 for the submerged rate. Catrawedarma I.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, existing correlations designed to predict the process parameters concentrate on the macroscopic aspects and lack insights into the trajectory of the liquid-solid flow within the riser [9][10]. Achieving a more thorough understanding of hydraulic transport to ensure dependable applications demands a more detailed approach.…”
Section: Introductionmentioning
confidence: 99%